Temozolomide Enhances Triple-Negative Breast Cancer Virotherapy In Vitro - Garza Morales, Rodolfo; González Ramos, Roxana; Chiba, Akiko; Montes de Oca Luna, Roberto; McNally, Lacey R.; McMasters, Kelly M.; Gomez Gutierrez, Jorge G (Molecular Diversity Preservation International, 2018)
Triple-negative breast cancer (TNBC) is one of the most aggressive types of cancer, and treatment is limited to chemotherapy and radiation. Oncolytic virotherapy may be a promising approach to treat TNBC. However, oncolytic adenovirus (OAd)-based mono-therapeutic clinical trials have resulted in modest outcomes. The OAd potency could be increased by chemotherapy-induced autophagy, an intracellular degradation system that delivers cytoplasmic constituents to the lysosome. In this study, the ability of alkylating agent temozolomide (TMZ)-induced autophagy to increase OAd replication and oncolysis in TNBC cells was evaluated. Human TNBC MDA-MB-231 and HCC1937 cells and mouse 4T1 cells were infected with an OAd expressing the red fluorescent protein mCherry on the virus capsid (OAdmCherry) alone or in combination with TMZ. TNBC cells treated with OAdmCherry/TMZ displayed greater mCherry and adenovirus (Ad) early region 1A (E1A) expression and enhanced cancer-cell killing compared to OAdmCherry or TMZ alone. The combined therapy-mediated cell death was associated with virus replication and accumulation of the autophagy marker light chain 3 (LC3)-II. Overall, this study provides experimental evidence of TMZ’s ability to increase oncolytic virotherapy in both human and murine TNBC cells.